2021
DOI: 10.1111/ajo.13352
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant dispensing before, during, and after pregnancy in New Zealand, 2005‒2014

Abstract: Background: Depression during pregnancy is associated with a number of negative impacts on maternal and infant health, therefore good control of depression in pregnant women is crucial. There is a lack of population-level information about patterns of antidepressant use during pregnancy in New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 28 publications
(30 reference statements)
8
12
2
Order By: Relevance
“…Previous studies have shown large-scale cessation during pregnancy, thought to be related to an unwillingness to prescribe antidepressants due to potential risks their use poses to the foetus (Grigoriadis et al, 2014;Huang et al, 2014;Roerecke et al, 2013;Udechuku et al, 2010). Compared to previous research, the reduction in use observed in this study is negligible (Donald et al, 2021;Jimenez-Solem et al, 2013;Petersen et al, 2011;Ramos et al, 2007;Zoega et al, 2015). However, while we observed stable use over pregnancy in our sample, we were unable to determine what the pre-pregnancy dispensing prevalence was like nor whether there was a reduction from trimesters two to three, as this information was not collected.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…Previous studies have shown large-scale cessation during pregnancy, thought to be related to an unwillingness to prescribe antidepressants due to potential risks their use poses to the foetus (Grigoriadis et al, 2014;Huang et al, 2014;Roerecke et al, 2013;Udechuku et al, 2010). Compared to previous research, the reduction in use observed in this study is negligible (Donald et al, 2021;Jimenez-Solem et al, 2013;Petersen et al, 2011;Ramos et al, 2007;Zoega et al, 2015). However, while we observed stable use over pregnancy in our sample, we were unable to determine what the pre-pregnancy dispensing prevalence was like nor whether there was a reduction from trimesters two to three, as this information was not collected.…”
Section: Discussioncontrasting
confidence: 98%
“…First, antidepressant prevalence among pregnant New Zealand women would be in line with the international prevalence estimates (Molenaar et al, 2020). Second, antidepressant use would substantially decrease across trimesters, consistent with global trends (Donald et al, 2021;Jimenez-Solem et al, 2013;Petersen et al, 2011;Ramos et al, 2007;Zoega et al, 2015). Third, women aged ⩾ 35 years would show the highest percentage of antidepressant use across pregnancy, consistent with previous research, as well as evidence that antidepressant use increased with increasing age in NZ (Donald et al, 2021;Jimenez-Solem et al, 2013;Ramos et al, 2007;Donald et al, 2021;Wilkinson and Mulder, 2018).].…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations